WHEN THERE WAS MORE DEMOCRACY IN LITHUANIA? A COMPARISON OF THE POLITICAL REGIMES OF THE FIRST AND SECOND REPUBLICS OF LITHUANIA - NORKUS, ZENONAS (Politologija, 2012)
The article provides a diachronic quantitative comparison of the political regimes of the First (interwar, LR I) and Second (contemporary, LR II) Republics of Lithuania, which is supplemented by a synchronic comparison with neighbour countries. For this comparison, the data set and the Index of Democracy by the Finnish political scientist Tatu Vanhanen (known in the literature as the Vanhanen Index, VI) is used; its values are calculated by multiplying those of the indicators of public contestation and of the participation in elections. The Vanhanen data are corrected, extended, and some of his assumptions are criticised. Vanhanen’s index is not a valid tool for measuring liberal democracy. However, the application of Vanhanen’s index to the time of the 1926 coup helps to highlight in the decorative parliamentarism of the IV Seimas in 1936–1940 some non-fictive elements of the genuine electoral regime, which have survived because of the obstacles to the complete entrenchment of authoritarianism, set by the autonomy of the Klaipėda region under defense of international treaties.